Performance Evaluation of Reference Reflections in Polymer Optical Fibers for Strain Sensing - Dengler, S. A.; Gonzalez, R. V.Roseeu; Luber, M.; Ziemann, O.; Engelbrecht, R.; Schmauß, Bernhard (Optics InfoBase Conference Papers, 2022)
We present a robust concept for quasi distributed strain measurement using optical time domain reflectometry (OTDR) in polymer o pticalfibers (P OF). The spatial shifts of discrete reflective e vents in the OTDR trace are e valuated as reference points. It is shown how such reference reflections can be prepared and which properties can be expected.
CRIS-Team Scopus Importer:2024-12-16